Hormonal trends in patients suffering from long COVID symptoms - Sunada, Naruhiko; Honda, Hiroyuki; Nakano, Yasuhiro; Yamamoto, Koichiro; Tokumasu, Kazuki; Sakurada, Yasue; Matsuda, Yui; Hasegawa, Toru; Otsuka, Yuki; Obika, Mikako; Hanayama, Yoshihisa; Hagiya, Hideharu; et al. (Endocrine Journal, 2022)
Symptoms of long COVID are complex and long-lasting, and endocrine dysfunction might be involved in the underlying mechanisms. In this study, to clarify the hormonal characteristics of long COVID patients, laboratory data for patients who visited the outpatient clinic for long COVID were evaluated. A retrospective analysis was performed for patients who visited Okayama University Hospital during the period from Feb 2021 to Dec 2021 with focus on the interrelationships between major symptoms and endocrine data. Information and laboratory data were obtained from medical records for 186 patients. The patients had various symptoms, and the most frequent symptoms were general malaise, dysosmia/dysgeusia, hair loss, headache, dyspnea, and sleeplessness. Patients who were suffering from fatigue and dysosmia/dysgeusia were younger, while hair loss was more frequent in older and female patients. As for the characteristics of patients suffering from general fatigue, the scores of depression and fatigue were positively correlated with serum levels of cortisol and free thyroxin (FT4), respectively. Also, patients suffering from general fatigue had lower levels of serum growth hormone and higher levels of serum FT4, while patients with dysosmia/dysgeusia had a significantly lower level of serum cortisol. Serum thyrotropin (TSH) levels were higher and the ratios of FT4/TSH were lower in the initially severe cases, suggesting occult hypothyroidism. In addition, the ratios of plasma adrenocorticotropin to serum cortisol were decreased in patients with relatively high titers of serum SARS-CoV-2 antibody. Thus, hormonal changes seem to be, at least in part, involved in the persistent symptoms of long COVID.